Self Accounting System dalam perspektif Al-Qur’an: Sarana Pendidikan untuk mewujudkan Manusia sebagai khalifah dimuka Bumi - Ikhsan, Addinul; Panorama, Maya; Badaruddin, KMS (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This study aims to identify and analyze the concept of self-accounting system in the perspective of the Qur'an as a means of education to realize humans as khalifah on earth. This study uses a qualitative method that describes the concepts and types of library research, namely research whose object of study uses library data in the form of books as the data source. The results of this study are the concept of self-accounting system (self-accounting) is a form of scientific and technological development that does not conflict with the perspective of the Qur'an and through this concept can remind humans about their existence as caliphs on earth; The concept of a self-accounting system plays a very important role as a means of improving the quality of education because it can become an applied concept as a means of improving education in families, schools and communities; Changes and challenges in the application of the concept of self-accounting system in the era of globalization is a necessity that must be faced. The development of technological science has been applied to support that the concept can be relevant as a medium to help develop the world of Islamic religious education.Â